Mechanisms of head stability during gait initiation in young and older women: A neuro-mechanical analysis. (February 2018) - Maslivec, A.; Bampouras, T.M.; Dewhurst, S.; Vannozzi, G.; Macaluso, A.; Laudani, L.
Abstract: Decreased head stability has been reported in older women during locomotor transitions such as the initiation of gait. The aim of the study was to investigate the neuro-mechanical mechanisms underpinning head stabilisation in young and older women during gait initiation. Eleven young (23.1 ± 1.1 yrs) and 12 older (73.9 ± 2.4 yrs) women initiated walking at comfortable speed while focussing on a fixed visual target at eye level. A stereophotogrammetric system was used to assess variability of angular displacement and RMS acceleration of the pelvis, trunk and head, and dynamic stability in the anteroposterior and mediolateral directions. Latency of muscle activation in the sternocleidomastoid, and upper and lower trunk muscles were determined by surface electromyography. Older displayed higher variability of head angular displacement, and a decreased ability to attenuate accelerations from trunk to head, compared to young in the anteroposterior but not mediolateral direction. Moreover, older displayed a delayed onset of sternocleidomastoid activation than young. In conclusion, the age-related decrease in head stability could be attributed to an impaired ability to attenuate accelerations from trunk to head along with delayed onset of neck muscles activation.